Pola Perkembangan Bahasa Anak Usia Dini dalam Perspektif Pendidikan Islam - Yuli Ani Setyo Dewi (Program Studi PGRA, 2015)
This paper aims to understand the patterns of early childhood language development in Islamic education. Early childhood education in the Islamic view is to maintain, promote the growth and nature of which are owned by the child.While the purpose of early childhood education in Islam is to instill Islamic values early on. Early childhood education aims to develop the full potential of the child (the whole child) so that later can function as a whole human being. A language is a communication tool that is used to convey meaning to someone with the order of words that are easy to understand. So in conveying something by using the right language is very important. In early childhood, language capability continues to evolve. The role of parents and teachers as well as people around the environment will impact a remarkable development. Parents and teachers should set an example and a good speech to their children in accordance with the teachings of the religion of Islam which every spoken word we must say with good language, manners and also easily understood by children.So that the children's language development will be able to thrive according to the teachings of our religious education. In the future development is expected to be a human child as true, faithful and devoted to God